THE REASONING BEHIND THE PHILIPPINES' STRATEGY TO COMBAT GLOBAL TERRORISM UNDER THE ADMINISTRATION OF PRESIDENT RODRIGO DUTERTE (2016-2018) - Rachel Kumendong (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2020)
Since 2014, the Islamic State (IS) has emerged as one of the deadliest threats to world peace and security, as evidenced by the increasing number of terrorist attacks carried out by IS worldwide, and the number of fatalities caused by these attacks. IS established its strongholds in Iraq and Syria and is determined to create a global caliphate through the creation of IS wilayats across the world. In 2016, IS began to weaken and lose territory in the Middle East which resulted in it strengthening its power in Southeast Asia by forming a wilayat in the Southern Philippines.The presence of IS in the Philippines has been perceived as a national security threat in the country. President Rodrigo Duterte has formulated a national strategy to combat global terrorism in the country. This study aims to determine the strategy to eradicate global terrorism in the Philippines and explain the considerations behind the formation of that strategy. This research uses neoclassical realist perspective with major concepts named national security, national interests, terrorism, and counterterrorism. The methodology used is a qualitative descriptive research methodology that provides detailed explanations and a thorough analysis. The results of this study found five strategies to eradicate global terrorism in the Philippines, namely the importance of using military force, supported by strengthening laws on terrorism, security alliances, social rehabilitation, and regional cooperation. Furthermore, the existence of these strategies derives from three main reasons, namely the increasing prevalence of IS in the Philippines, the siege of Marawi, and maritime security in the tri-border area.Bahasa Indonesia Abstract: Sejak tahun 2014, Islamic State muncul sebagai salah satu ancaman paling mematikan bagi keamanan dan perdamaian dunia, dibuktikan dengan meningkatnya jumlah serangan terorisme yang dilakukan oleh IS di seluruh dunia, diikuti dengan banyaknya korban jiwa yang disebabkan oleh serangan-serangan tersebut. Kelompok teroris internasional ini berbasis di Iraq dan Syria dan bertujuan untuk membangun khilafah global melalui pembentukan wilayat-wilayat yang tersebar di seluruh dunia. Pada tahun 2016, kondisi IS mulai melemah dan mulai kehilangan daerah kekuasaannya di Timur Tengah sehingga mendesak IS untuk memperkuat kekuatannya di Asia Tenggara dengan membentuk wilayat di Filipina Selatan. Kehadiran IS di Filipina telah dinyatakan sebagai ancaman bagi kemanan nasional. Pemerintah Filipina di bawah pemerintahan Presiden Rodrigo Duterte merumuskan strategi keamanan nasional untuk memberantas ancaman terorisme global di negara tersebut. Penelitian ini bertujuan untuk mengetahui strategi pemberantasan terorisme global Filipina tersebut dan menjelaskan pertimbangan-pertimbangan di balik pembentukan strategi tersebut. Perspektif yang digunakan ialah neoklasikal realis dengan konsep-konsep seperti keamanan nasional, kepetingan negara, terorisme, dan kontra-terorisme. Metodologi yang digunakan adalah metodologi penelitian deskriptif kualitatif yang memberikan penjelasan detil serta analisis yang menyeluruh. Hasil penelitian ini menemukan adanya lima strategi pemberantasan terorisme global di Filipina yaitu keutamaan penggunaan kekuatan militer, didukung dengan penguatan hukum mengenai terorisme, aliansi keamanan, rehabilitasi sosial, dan kerjasama regional. Selanjutnya, keberadaan startegi-strategi ini derangkat dari tiga asalan utama yaitu meningkatnya prevalensi IS di Filipina, pengepungan Kota Marawi, dan keamanan maritim di tri-border area.